(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
This Research Examines British Policy Towards the 1919 Revolution in Egypt, a pivotal event in the country’s History. it Begins by Examining Precursors to the Revolution, which Included the Declaration of the British Protectorate over the country in 1914 and the Arrest by British Authorities of a Number of National Leaders who had Nominated Themselves to Represent Egypt at the Paris Pace Conference. It Also Provides a Brief Overview of the General Situation in Egypt During the Revolution and the Events that the Country Witnessed. the Research then clarifies the measures Taken by the British Authorities to Suppress the Revolution, starting with violence Inflicted on Demonstrators and the Arrest Campaigns Targeting the country national Elite at the Beginning of the Revolution It also Discusses the Policy of Appeasement Adopted by the British government to Resolve the Egyptian Question, Focusing on the Role General Allenby in calming the Situation, the dispatch of the Millner Commission, and the Negotiations that took Place Between the National Leaders and Egyptian Government, Culminating in Britain Issuance of the February 28 Declaration, Which Recognized Egypt As An Independent State While Maintaining a Lot of Restrictions.